MODELLING THE LAND USE AND LAND COVER CHANGES IN PORTUGAL: A MULTI-SCALE AND MULTI-TEMPORAL APPROACH - Bruno M. Meneses; Eusébio Reis; Maria J. Vale; Rui Reis (Finisterra - Revista Portuguesa de Geografia, 2018)
The Portuguese territory has undergone a relevant land use and land cover changes (LUCC) over the past decades. The land use and land cover (LUC) datasets revision and new datasets production allow us to understand LUCC over time. This study goes further into this analysis using the most recent LUC datasets, covering the whole Portuguese continental area, from 1990 to 2012 and presents innovative knowledge that helps understanding LUC dynamics within this period. It shows that the trends inducing spatial variation within different LUC classes changed over time, revealing different spatial and temporal dynamics of these LUCC in the Portuguese territory. The main LUCC are related to the reduction of forest and certain types of agricultural areas, and an increase in urban areas, but the main LUCC assume different dynamics when taken at the regional scale (NUTS II). Future tendencies within LUCC are also estimated using CA-Markov, and the results point out the tendency of increase and decrease of the LUC types previously mentioned. The areas of LUC datasets with different properties were compared and large area discrepancies were observed for some LUC classes. These assessments are relevant results for the evaluation and understanding of LUCC and namely for the Portuguese planning process in the near future.